For both problems, we can use the section formula.
1) ![P=\left(\frac{(1)(1)+(5)(-9)}{6}, \frac{(1)(8)+(5)(3)}{6} \right)=\boxed{\left(-\frac{22}{3}, \frac{23}{6} \right)}](https://tex.z-dn.net/?f=P%3D%5Cleft%28%5Cfrac%7B%281%29%281%29%2B%285%29%28-9%29%7D%7B6%7D%2C%20%5Cfrac%7B%281%29%288%29%2B%285%29%283%29%7D%7B6%7D%20%5Cright%29%3D%5Cboxed%7B%5Cleft%28-%5Cfrac%7B22%7D%7B3%7D%2C%20%5Cfrac%7B23%7D%7B6%7D%20%5Cright%29%7D)
2) ![Z=\left(\frac{(2)(7)+(1)(1)}{3}, \frac{((2)(5)+(1)(2)}{3} \right)=\boxed{(5, 4)}](https://tex.z-dn.net/?f=Z%3D%5Cleft%28%5Cfrac%7B%282%29%287%29%2B%281%29%281%29%7D%7B3%7D%2C%20%5Cfrac%7B%28%282%29%285%29%2B%281%29%282%29%7D%7B3%7D%20%5Cright%29%3D%5Cboxed%7B%285%2C%204%29%7D)
9 students
30% ends up being .3%, multiply .3% by 30 students which equals 9.
The square roots of 64 is A B and C.
Answer: X=8
Step-by-step explanation:
168/6=28. x+20=28. 8+20=28.
6(8+20)=168
This has to be done by hit and trial method. i.e. you have to checking adding which of the function from first column to function in second column will yield h(x).
The following functions yield given value of h(x).
f(x) = -2x + 3
g(x) = 7x - 9
f(x) + g(x) = -2x +3 + 7x - 9
f(x) + g(x) = 5x -6 = h(x)
So, from 1st column its the cell number 3, and from the second column its the cell number 2.